Macrophage Polarization States in the Tumor Microenvironment - Boutilier, Ava J.; Elsawa, Sherine F. (International journal of molecular sciences, 2021)
The M1/M2 macrophage paradigm plays a key role in tumor progression. M1 macrophages are historically regarded as anti-tumor, while M2-polarized macrophages, commonly deemed tumor-associated macrophages (TAMs), are contributors to many pro-tumorigenic outcomes in cancer through angiogenic and lymphangiogenic regulation, immune suppression, hypoxia induction, tumor cell proliferation, and metastasis. The tumor microenvironment (TME) can influence macrophage recruitment and polarization, giving way to these pro-tumorigenic outcomes. Investigating TME-induced macrophage polarization is critical for further understanding of TAM-related pro-tumor outcomes and potential development of new therapeutic approaches. This review explores the current understanding of TME-induced macrophage polarization and the role of M2-polarized macrophages in promoting tumor progression.